PENGENDALIAN INTERNAL DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN SERTA DAMPAKNYA KEPADA RUMAH SAKIT BHAYANGKARA KEDIRI - Agustin, Beby Hilda (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.10.TAHUN.2021, 2021)
The effect of internal control consists of control environment variables, risk assessment, control procedures, information and communication and very important monitoring. This study used a sample of 179 patients who underwent surgery in the operating room of the Bhayangkara Kediri Hospital. Meanwhile, the sampling used purposive sampling method. Data analysis using path analysis. The results of this study using path analysis showed that there was an influence between internal control (X1) on patient satisfaction (Y1) of 0.471, the effect of service quality (X2) on patient satisfaction (Y1) was 0.248, the effect of patient satisfaction (X1) on feedback (Y2) is 0.650, the effect of internal control (X1) through patient satisfaction (Y1) on feedback (Y2) is 0.306, the effect of service quality (X2) through patient satisfaction (Y1) on feedback (Y2) is 0.161. The results of this study also indicate a simultaneous influence between internal control variables and service quality on patient satisfaction and feedback.